Study of lichen (Usnea spp.) as a traditional medicine in Bogor, West Java - Miftahul Jannah; Nida Afifah; Muhammad Rifqi Hariri; Anisa Rahmawati; Tri Yuni Indah Wulansari (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
Usnea is a genus of lichen used as a traditional medicine in the form of herbal medicine. The people of Bogor know Usnea as kayu angin, antanan, and cecenetan. Usnea used in herbal medicine is often considered only one species, even though there are many different species. Information about the traditional use of Usnea is essential to increase the widespread use of natural resources. This study purposed to determine the types of Usnea and their use as traditional medicine by the people of Bogor city. A total of 30 respondents were interviewed using semi-structured questionnaires and personal interviews. Data were analyzed descriptively based on the results of exploration and interviews with respondents. The results showed that six species of Usnea had been used for treatment, including U. intermedia, U. esperantiana, U. hesperina, U. pectinata, U. fragilescens, and U. baileyi. Usnea is used for health herbs, after childbirth, colds, gout, and herbal mixtures in all medications